2011
DOI: 10.1111/j.1471-6712.2011.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors of importance for self‐reported mental health and depressive symptoms among ages 60–75 in urban Iran and Sweden

Abstract: 1088 participants were approached (668 Iranians in Iran; 105 immigrated Iranians in Sweden; and 305 Swedes in Sweden). Factors effecting self-reported mental health was self-reported health, smoking, satisfaction with social life and also a sense of connection to ones cultural roots and traditions. Also demographic variables such as group belonging (Swedes vs. Iranians), sex and satisfaction with Income were shown to be important when performing the regression analysis. In the chi-square analysis the Iranian s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Moreover, recent studies by Momeni et al54 and Cuypers et al55 emphasize that social relations seem to be an important factor influencing mental health in old age. Therefore, it is important for health professionals to both observe and promote the mental health of those aged 65 to 74 years, so that they focus on social relations in their daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies by Momeni et al54 and Cuypers et al55 emphasize that social relations seem to be an important factor influencing mental health in old age. Therefore, it is important for health professionals to both observe and promote the mental health of those aged 65 to 74 years, so that they focus on social relations in their daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety are the most common mental disorders among older adults . Depression and anxiety are not strictly defined, and the diagnosis of these disorders is based on diagnostic criteria and the use of various assessment scales.…”
Section: Introductionmentioning
confidence: 99%
“…Being female, age, no longer being married, length of stay in a nursing home , low level of education and the presence of comorbid illnesses are reported to be associated with depression and anxiety among older people in general. Considering these factors is therefore important in exploring anxiety and depression symptoms among nursing home residents.…”
Section: Introductionmentioning
confidence: 99%
“…Both Iranian groups showed substantially higher symptom levels than the native group, but they differed in their health behavior and worries. For example, Iranians in Sweden were less worried and sought more treatment for depression than Iranians in Iran (Momeni, Wettergren, Tessma, Maddah, & Emami, 2011). De Jong et al (2011 analyzed trauma-related mental health symptoms and health complaints among Somali women living in acute war conditions in Mogadishu, and found that trauma exposure was associated with somatic health complaints rather than PTSD.…”
mentioning
confidence: 99%